Voxel-based morphometry analyses of in vivo MRI in the aging mouse lemur primate - Sawiak, Stephen J.; Picq, Jean-Luc; Dhenain, Marc (Frontiers in Aging Neuroscience, 2014)
Cerebral atrophy is one of the most widely brain alterations associated to aging. A clear relationship has been established between age-associated cognitive impairments and cerebral atrophy. The mouse lemur (Microcebus murinus) is a small primate used as a model of age-related neurodegenerative processes. It is the first nonhuman primate in which cerebral atrophy has been correlated with cognitive deficits. Previous studies of cerebral atrophy in this model were based on time consuming manual delineation or measurement of selected brain regions from magnetic resonance images (MRI). These measures could not be used to analyse regions that cannot be easily outlined such as the nucleus basalis of Meynert or the subiculum. In humans, morphometric assessment of structural changes with age is generally performed with automated procedures such as voxel-based morphometry (VBM). The objective of our work was to perform user-independent assessment of age-related morphological changes in the whole brain of large mouse lemur populations thanks to VBM. The study was based on the SPMMouse toolbox of SPM 8 and involved thirty mouse lemurs aged from 1.9 to 11.3 years. The automatic method revealed for the first time atrophy in regions where manual delineation is prohibitive (nucleus basalis of Meynert, subiculum, prepiriform cortex, Brodmann areas 13-16, hypothalamus, putamen, thalamus, corpus callosum). Some of these regions are described as particularly sensitive to age-associated alterations in humans. The method revealed also age-associated atrophy in cortical regions (cingulate, occipital, parietal), nucleus septalis, and the caudate. Manual measures performed in some of these regions were in good agreement with results from automatic measures. The templates generated in this study as well as the toolbox for SPM8 can be downloaded. These tools will be valuable for future evaluation of various treatments that are tested to modulate cerebral aging in lemurs.